Diagnosing and preventing iron overload - Ramanathan, G.; Olynyk, John; Ferrari, P. (2017)
Absolute or functional iron (Fe) deficiency is an important determinant of anemia in hemodialysis patients and parenteral Fe is routinely used to treat this condition in conjunction with erythropoiesis stimulating agents. While restoration of hemoglobin toward the target range is a good outcome of Fe replacement, it is well known that Fe overload and toxicity may be adverse consequences of this therapy. Dialysis clinical practice guidelines recommend tailoring Fe therapy based on transferrin saturation and serum ferritin levels. Unfortunately, serum Fe markers may not accurately reflect the amount of Fe in the body, because factors such as infections, inflammation, or malignancy can alter serum ferritin levels. Some recent trials in dialysis patients receiving high intravenous Fe doses have shown increased cardiovascular morbidity and mortality and studies using magnetic resonance imaging (MRI) in this population have shown excessive tissue liver iron content (LIC) suggesting Fe overload. While LIC measured by MRI correlates well with LIC quantitated by liver biopsy, it only represents a surrogate marker for total body Fe and its clinical relevance in dialysis patients in terms of mortality and morbidity remains to be demonstrated. Nevertheless, these recent findings challenge the use of current serum Fe markers recommended by clinical guidelines to guide safe Fe therapy in dialysis patients. While not yet established for the routine screening of dialysis patients for Fe overload, MRI should be considered in patients who have received a high cumulative dose of intravenous Fe, or have long cumulative dialysis vintage. Further studies are needed to assess how MRI will alter management.